The Changes of pH, Conductivity, And Dissolved Oxygen in Cyanobacteria Arthrospira platensis Culture with the Presence of Environmental Pollutants - Tan, Ziyin (2017)
Large amount of pollutants such as heavy metal, light metal, and pesticides are released into environment which led to environmental pollution Thus a simple, rapid and low cost bioindicator are required to screen these pollutants in aquatic environment. Whole cell bioindicators can be an effective and fast detection method as they are highly sensitive and inexpensive to screen the pollutants. The main objective of this project was to determine the changes of parameters such as pH, conductivity, dissolved oxygen in A. platensis with presence of Pb, Cd, Al, Li, parathion and atrazine. Five mL of A. platensis cells from day 4 culture were exposed to different concentration of pollutants (0.010 mg/L, 0.100 mg/L, and 1.000 mg/L). Then, the pH level, conductivity level, and dissolved oxygen level were determined by pH meter, conductivity electrode, and oxygen electrode respectively in every 0th hour, 1th hour, 2nd hour, 6th hour and 24th hour. The results showed the pH level, conductivity level increased, and decreased in dissolved oxygen level as increased in concentration of pollutants. This was because A. platensis unable to undergo photosynthesis due to depletion of O2 and nutrients, therefore the A. platensis couldn’t survived in the presence of pollutants. This experiment was carried out successfully and the potential of A. platensis as a whole cell biondicator to detect the environmental pollutants was determined.